PENGARUH AUDIT COMMITTEE, CASH HOLDING, DAN FAKTOR-FAKTOR LAINNYA TERHADAP PERATAAN LABA - Silaban, Nico Chandra; Marlinah, Aan; Supriatna, Dicky (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aim of this research is to empirically prove that company size, profitability, dividend policy, leverage, audit committee, cash holding and institutional ownership are able to predict the probability of company management implementing income smoothing practices. This research uses a population of companies in the consumer cyclicals and consumer non-cyclicals sectors that have been listed on the Indonesia Stock Exchange from 2017 to 2022, with 34 companies selected as samples. The sample was selected using a purposive sampling method and analyzed using the logistic regression method. The results of this research show that company size, dividend policy, leverage, audit committee, cash holding, and institutional ownership cannot predict the probability of company management implementing income smoothing practices, while profitability can predict the probability of company management implementing income smoothing practices.